Scoliosis in Duchenne’s muscular dystrophy: a changing trend in surgical management: A historical surgical outcome study comparing sublaminar, hybrid and pedicle screw instrumentation systems - Arun, Ranganathan (Springer-Verlag, 2009)
A non-randomised retrospective study to compare the results of surgical correction of scoliosis in Duchenne’s muscular dystrophy (DMD) patients using three different instrumentation systems—Sublaminar instrumentation system (Group A), a hybrid of sublaminar and pedicle screw systems (Group B) and pedicle screw system alone (Group C). Between 1993 and 2003, 43 patients with DMD underwent posterior spinal fusion and instrumentation. Group A (n = 19) had sublaminar instrumentation system, Group B (n = 13) had a hybrid construct and Group C (n = 11) was treated with pedicle system. The mean blood loss in Group A was 4.1 l, 3.2 l in Group B and 2.5 l in Group C. Average operating times in Group A, B and C were 300, 274 and 234 min, respectively. Mean pre-operative, post-operative and final Cobb angle in Group A was 50.05 ± 15.46°, 15.68 ± 11.23° and 21.57 ± 11.63°, Group B was 17.76 ± 8.50°, 3.61 ± 2.53° and 6.69 ± 4.19° and Group C was 25.81 ± 9.94°, 5.45 ± 3.88°, 8.90 ± 5.82°, respectively. Flexibility index or the potential correction calculated from bending radiographs were 60 ± 6.33, 70 ± 4.65 and 67 ± 6.79% for Group A, Group B and Group C respectively. The percentage correction achieved was 72.5 ± 14.5% in Group A, 82 ± 6% in Group B and 82 ± 8% in Group C. The difference between percentage correction achieved and the flexibility index was 12.45 ± 8.22, 12.05 ± 1.3 and 15.00 ± 1.21% in Group A, B and C, respectively The percentage loss of correction in Cobb angles at final follow-up in Group A, B and C was 12.5 ± 3.5, 16.5 ± 1. and 12.5 ± 2.5%, respectively. Complications seen in Group A were three cases of wound infection and two cases of implant failure; Group B had a single case of implant failure and Group C had one patient with wound infection and one case with a partial screw pull out. Early surgery and smaller curve corrections appears to be the current trend in the management of scoliosis in DMD. This has been possible due to early curve detection and surgery thus having the advantage of less post-operative respiratory complications and stay in paediatric intensive care. Also, early surgery avoids development of pelvic deformity and extension of instrumentation to the pelvis thereby reducing blood loss. This trend reflects the advent of newer and safer instrumentation systems, advanced techniques in anaesthesia and cord monitoring. Sublaminar instrumentation system group had increased operating times and blood loss compared to both the hybrid and pedicle screw instrumentation systems due to increased bleeding from epidural vessels and pelvic instrumentation. Overall, the three instrumentation constructs appear to provide and maintain an optimal degree of correction at medium to long term follow up but the advantages of lesser blood loss and surgical time without the need for pelvic fixation seem to swing the verdict in favour of the pedicle screw system.